A new species of cave catfish from Brazil, Trichomycterus rubbioli sp.n., from Serra do Ramalho karstic area, São Francisco River basin, Bahia State (Silurifomes: Trichomycteridae) - Bichuette, Maria Elina; Rizzato, Pedro Pereira (Zootaxa, 2012)
Trichomycterus rubbioli, herein described, is a new species from the limestone caves of the Água Clara system from theSerra do Ramalho karstic area, southwest of Bahia State, north-eastern Brazil. The new species is diagnosed by the com-bination of the following non-exclusive characters: highly reduced skin pigmentation; reduced eyes, externally visible assmall black or reddish-brown spots; long barbels, especially the nasal (86.9–127.1% of head length) and maxillary (98.1–129.3% of head length); and pectoral-fin ray count reaching I, 9. The troglobitic status is suggested by the presence oftroglomorphisms on an advanced degree, especially the reduction of skin pigmentation and the regression of the eyes, be-sides the absence of individuals in superficial drainages of the region. Population densities, recorded on two occasions,were extremely low. Trichomycterus rubbioli occurs in water bodies formed by infiltration in the rock, and, because of this, it must be considered fragile and as a priority in conservation programs of Brazilian karstic areas.